Swiss Democracy - Linder, W. author. aut Link
XXI, 210 p.
Keywords: An authoriative analysis of Swiss democracy, the institutions of federalism, and consensus democracy through political power sharing. Linder analyses the scope and limits of citizen's participation in direct democracy, which distinguishes Switzerland most from parliamentary systems. Central and Eastern Europe and all countries with minority problems could learn much of value from this study.